Uji Efektivitas Ragam Pupuk Hayati untuk Meningkatkan Produktivitas Kedelai di Lahan Lebak - Marlina, Neni; Gusmiatun, Gusmiatun (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Soybeans are rich in protein and very appreciated by the public of Indonesia. However, soybeans decreased productivity and improved through the expansion of planting areas such as shallow swampy wetlands and the use of biofertilizers such as phosphate solubilizing bacteria (PSB), Azospirillum, mycorrhiza, and bio-organic fertilizer. The results of previous studies have shown that biofertilizer can increase rice productivity in lowland and tidal land. Furthermore, the biofertilizer can assist in providing the uptake of N and P and improve soybean productivity in the lowland area. Field research in shallow swampy areas in Ogan Ilir, South Sumatra Province. Random Group prepared five treatments with five replications. The treatments include biofertilizers, PSB, mycorrhiza, Azospirillum, and BOF. The results showed that the PSB, mycorrhiza, Azospirillum, and BOF can increase N nutrient absorption in a row 201.33%, 182.67%, 170.67%, 161.33%, P nutrients 357.89%, 273.68%, 173,68%, 142,40%, soybean production respectively 228.00%, 208.00%, 201.33%, and 194.67% compared without biofertilizer